User experience of the Written Exam Question Quality tool to inform the writing of new written-exam questions - Vachon Lachiver, Elise; St-Onge, Christina (Canadian Medical Education Journal, 2024)
Background: Creating new written-exam questions is a burdensome task for faculty members. While several guidelines exist, there had not been a previous attempt to streamline them in a user-friendly tool. We created the Written Exam Question Quality tool (WEQQ) and explored potential users’ perception of this tool when writing their exam questions. Methods: We conducted a descriptive study to explore how four Canadian faculty members used the WEQQ. We conducted structured interviews that were analyzed within and across participants to understand the latter’s perceived usefulness and acceptability of the WEQQ. Quantitative data from a short questionnaire on creating exam questions and their psychometric properties were also collected. Results and conclusion: Participants’ perception of the WEQQ was positive, and they were favorable to its use. The WEQQ seemed to represent a user-friendly, easy way to help faculty members in creating multiple-choice or short-answer questions. Time on task remained the same when using the WEQQ. We were able to identify two user profiles, passive and active, which indicated how faculty members use the WEQQ to create exam questions. Future steps would be to further investigate if the WEQQ can increase the quality of written-exam questions and to understand how to promote an active use of the WEQQ when implementing this tool.